2020
DOI: 10.1038/s41598-020-63926-4
|View full text |Cite
|
Sign up to set email alerts
|

A proximity-labeling proteomic approach to investigate invadopodia molecular landscape in breast cancer cells

Abstract: Supplementary Table S1: List of proteins biotinylated by Tks5-BirA* fusion protein. Protein list results from the comparison of proteins biotinylated by Tks5-BirA* fusion protein with proteins biotinylated by BirA* control protein, after their isolation by affinity capture and identification by mass spectrometry. Proteins listed here correspond to proteins above the full line indicative of protein hits obtained at a pFDR of 1% on Fig.3A volcano plot. For each protein their link to invadosome, their implication… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 87 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…They also showed that, when constitutively active SRC is present, TKS4 accumulates in podosomes (actin-rich membrane protrusions involved in cell motility, see below) while forming a complex with SRC and cortactin [9]. TKS5 has also been reported to bind cortactin and other proteins important in the regulation of actin cytoskeleton assembly, including N-WASP, non-catalytic region of tyrosine kinase adaptor protein (NCK), and GRB2 (for a full list, see Table 1b) [10,29,52,78,79].…”
Section: Unknownmentioning
confidence: 99%
“…They also showed that, when constitutively active SRC is present, TKS4 accumulates in podosomes (actin-rich membrane protrusions involved in cell motility, see below) while forming a complex with SRC and cortactin [9]. TKS5 has also been reported to bind cortactin and other proteins important in the regulation of actin cytoskeleton assembly, including N-WASP, non-catalytic region of tyrosine kinase adaptor protein (NCK), and GRB2 (for a full list, see Table 1b) [10,29,52,78,79].…”
Section: Unknownmentioning
confidence: 99%
“…Coverslips coated with Oregon Green 488-conjugated gelatin (Life technologies, ThermoFisher) were prepared as described in Thuault et al [ 30 ]. After seeding for 4 h on gelatin-coated coverslips rehydrated in complete growth medium for 1 h before use, cells were fixed with a solution of 4% formaldehyde in PBS, permeabilized with 0.1% Triton X-100, and blocked with 1% BSA.…”
Section: Methodsmentioning
confidence: 99%
“…Since protein expression and function are influenced by post-transcriptional regulations, DNA/RNA sequencing cannot provide a full view of the process of metastases. Current proteomic technologies were used to identify and characterize the molecular components of the invadopodia linked to the metastatic progression of BC cells [182]. High throughput protein arrays have also been used to compare proteins expression between normal and malignant breast tissue with some interesting findings [183].…”
Section: Future Perspectivesmentioning
confidence: 99%